Penegakan Hukum Terhadap Kejahatan Ilegal Penambangan Mikro (IoT Devices) - Christian Felix Lumbanraja; Emmilia Rusdiana (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
This study aims to analyze the enforcement of criminal law against illegal micro-mining crimes committed through Internet of Things (IoT) devices, which represent a new form of cybercrime utilizing computing power without authorization. The research employs a normative juridical method with a statute, conceptual, and comparative approach, analyzing Indonesian criminal law provisions, particularly the Electronic Information and Transactions Law (UU ITE), the new Criminal Code (KUHP 2023), and the Personal Data Protection Law. The study finds that illegal micro-mining using IoT devices constitutes an unlawful exploitation of digital energy resources, yet remains unregulated explicitly in Indonesia’s positive law. The absence of clear norms regarding the unauthorized use of computing power creates obstacles in determining criminal responsibility and digital evidence admissibility. Therefore, the study concludes that a legal reform is needed to classify unauthorized cryptomining as a cybercrime, accompanied by the establishment of digital forensic standards specific to IoT environments to strengthen law enforcement capacity